MAPbI3 Deposition by LV-PSE on TiO2 for Photovoltaic Application - Smecca, Emanuele; Jena, Ajay Kumar; Deretzis, Ioannis; Valastro, Salvatore; Sanzaro, Salvatore; Mannino, Giovanni; Bongiorno, Corrado; La Magna, Antonino; Miyasaka, Tsutomu; Alberti, Alessandra (Frontiers in Electronics, 2021)
Hybrid perovskites are one of the most popular materials nowadays due to their very exclusive properties. To mitigate costs, complexity and environmental impact, in this work we have prepared Methylammonium lead Iodide (MAPbI3) films by a two-step Low-Vacuum Proximity-Space-Effusion (LV-PSE). The LV-PSE method exploits the low vacuum and the short diffusion path from the precursor source to have high thermal energy and partial pressure of the sublimated species close to the substrate. To this aim, the substrate is located at medium distance (2 cm) from the melting pots in a low vacuum chamber at 4x10-2 mbar. In the first step a PbI2 film is deposited on a substrate and in the second step the conversion into MAPbI3 occurs via an adsorption-incorporation-migration mechanism through the evaporation of methylammonium iodide (MAI) reagents. To exploit the potential of the conversion reaction, 180nm MAPbI3 layers are deposited on TiO2 substrates. The layers were characterized in terms of crystal structure by X-Ray Diffraction (XRD) analyses, that showed the exclusive presence of MAPbI3 confirming the complete conversion of the PbI2 film. Scanning Electron Microscopy (SEM) analyses revealed a flat uniform pin-hole-free coverage of the substrates and a good conformational coverage of the TiO2 underlayer. Trasmission Electron Microscopy (TEM) analyses addressed the formation of the tetragonal phase and the absence of amorphous phase in the film. Spectroscopic Ellipsometry (SE) analyses were used to explore the optical properties and the stability of the MAPbI3 layer at different temperature and ambient conditions. As proof of concept, solar cell architectures were prepared using TiO2 as Electron Trasporting Layer (ETL), Spiro-OMeTAD as Hole Transporting Layer (HTL) and Au as contact to exploit the new up-scalable and clean deposition method. Using just 180 nm thick layers the best efficiency reached with this architecture is 6.30%.